Informing sea turtle outreach efforts to maximize effectiveness. (13th September 2019) - Swindall, Jessica E.; Ober, Holly K.; Lamont, Margaret M.; Carthy, Raymond R.
ABSTRACT: Most sea turtle (Cheloniidae) species worldwide are endangered or threatened, with threats causing harm to sea turtles predominantly human‐induced. Thus, prevention of further declines to these imperiled species will require alteration of human behaviors. Regulations, incentives, and environmental education are 3 strategies that could be used to alter human behavior. Our goal was to determine how to maximize effectiveness of one of these strategies—education efforts. We investigated knowledge deficiencies and light pollution behaviors of individuals living in a region with nesting sea turtles, in an effort to determine the best approach to promote sea turtle conservation. During 2014, we mailed a survey to 3, 000 property owners in 4 coastal counties in Florida, USA, to achieve 3 objectives: assess what topic areas were misunderstood; discern who had knowledge deficiencies; and determine who had adopted turtle‐friendly lighting practices. The best predictors of knowledge included geographic factors (county, proximity of residences to the beach), demographic characteristics (age), and behaviors (individual's beach visitation rates). One practice that can reduce harm to sea turtles was common: use of window treatments to reduce light pollution. However, other practices harmful to sea turtles were prevalent, including long durations of use of outdoor lighting and use of light bulbs with wavelengths that can disturb sea turtles. Our results suggest that educational efforts could be enhanced by specifically focusing on increasing awareness of the effects of human actions on sea turtles, targeting individuals who visit the beach infrequently and live far from it to foster greater connection with these ecosystems, and publicizing a variety of options that could reduce harm to sea turtles so individuals feel a sense of freedom of choice. © 2019 The Wildlife Society. Abstract : Education is one strategy that could be used to curtail negative effects of human actions on sea turtles. We found evidence that educational efforts may be most efficient when focused on increasing awareness of human behaviors on sea turtles, targeting individuals with limited connection to the beach, and promoting awareness of a variety of low‐cost turtle‐friendly lighting options.